2019
DOI: 10.26434/chemrxiv.10271090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catalytic Resonance Theory: Parallel Reaction Pathway Control

Abstract: Catalytic enhancement of chemical reactions via heterogeneous materials occurs through stabilization of transition states at designed active sites, but dramatically greater rate acceleration on that same active site is achieved when the surface intermediates oscillate in binding energy. The applied oscillation amplitude and frequency can accelerate reactions orders of magnitude above the catalytic rates of static systems, provided the active site dynamics are tuned to the natural frequencies of the surface che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…It was further predicted that oscillations need to be in approximate resonance with the surface reactions to achieve reaction enhancements. [9][10][11][12] DFT calculations by Shetty et al revealed electric field-dependent linear scaling relationships of adsorbates on metal surfaces imperative for the understanding of dynamic catalytic processes. 13 Cycling between a potential suitable for the non-Faradaic dehydration of FA to surfaceadsorbed CO and the Faradaic oxidative desorption to form CO 2 enhanced the activity by a factor of up to around 20 at frequencies of 100 Hz, 14 consistent with promotional effect observed by Adžić et al earlier.…”
Section: Introductionmentioning
confidence: 99%
“…It was further predicted that oscillations need to be in approximate resonance with the surface reactions to achieve reaction enhancements. [9][10][11][12] DFT calculations by Shetty et al revealed electric field-dependent linear scaling relationships of adsorbates on metal surfaces imperative for the understanding of dynamic catalytic processes. 13 Cycling between a potential suitable for the non-Faradaic dehydration of FA to surfaceadsorbed CO and the Faradaic oxidative desorption to form CO 2 enhanced the activity by a factor of up to around 20 at frequencies of 100 Hz, 14 consistent with promotional effect observed by Adžić et al earlier.…”
Section: Introductionmentioning
confidence: 99%
“…It was further predicted that oscillations need to be in approximate resonance with the surface reactions to achieve reaction enhancements. [9][10][11][12] DFT calculations by Shetty et al revealed electric field-dependent linear scaling relationships of adsorbates on metal surfaces imperative for the understanding of dynamic catalytic processes. 13 Cycling between a potential suitable for the non-Faradaic dehydration of FA to surfaceadsorbed CO and the Faradaic oxidative desorption to form CO 2 enhanced the activity by a factor of up to around 20 at frequencies of 100 Hz, 14 consistent with promotional effect observed by Adžić et al earlier.…”
Section: Introductionmentioning
confidence: 99%
“…We recently computationally demonstrated that the limit of a volcano curve can be overcome for a hypothetical unimolecular reaction (A ↔ B) by oscillating between two energetic states on either side of the volcano curve. [14][15][16][17] Achieved by shifting adsorbate binding energy, the catalytic system oscillates between two energetic states where either surface reaction or product desorption are rate determining. At sufficiently high oscillation frequency, the resulting time-averaged turnover frequency (TOF) is higher than the Sabatier maximum.…”
mentioning
confidence: 99%